Primary energy factor of a district cooling system - Duh Čož, Tjaša (Strojniški vestnik, 2016)
The primary energy efficiency for various energy-related processes can be calculated using the primary energy factor (PEF). In this paper, the PEFs of district cooling systems (PEF DC) for different types of cold production are derived. These concern cold production with an absorption chiller driven by different available sources and cold production with a compressor chiller driven by different types of engines and related energy sources. Based on the fundamental definition of the PEF, a mathematical model for calculating the PEF DC for different types of cold production was developed. The results in this study reveal that the PEF DC can be significantly improved in the case of combined cooling and power generation. The PEF DC in the case of combined cooling and power generation is lower than when cooling with electrically driven compressor chillers when the energy efficiency of the electricity generation in thermal power plant is low or the PEF of the electricity (PEF el) is high. In cold production technologies where coal is used as the primary energy source more primary energy is consumed compared to other primary energy sources (i.e. naturaThe primary energy efficiency for various energy-related processes can be calculated using the primary energy factor (PEF). In this paper, the PEFs of district cooling systems (PEF DC) for different types of cold production are derived. These concern cold production with an absorption chiller driven by different available sources and cold production with a compressor chiller driven by different types of engines and related energy sources. Based on the fundamental definition of the PEF, a mathematical model for calculating the PEF DC for different types of cold production was developed. The results in this study reveal that the PEF DC can be significantly improved in the case of combined cooling and power generation. The PEF DC in the case of combined cooling and power generation is lower than when cooling with electrically driven compressor chillers when the energy efficiency of the electricity generation in thermal power plant is low or the PEF of the electricity (PEF el) is high. In cold production technologies where coal is used as the primary energy source more primary energy is consumed compared to other primary energy sources (i.e. natural gas, waste heat, etc.).
Keywords: daljinsko hlajenje; faktor primarne energije; hladilniki; proizvodnja hladu